2021
DOI: 10.1016/j.radcr.2021.04.069
|View full text |Cite
|
Sign up to set email alerts
|

Gastrocnemius acrometastasis from muscle-invasive urothelial bladder carcinoma: A case report

Abstract: Urinary bladder carcinoma is a common malignancy worldwide. The metastatic disease to distant organs including lung, liver, and bone is well established. However, metastasis to below-knee-level; also known as acrometastasis is a rare occurrence and occurs approximately 0.1% of all bone metastases. It is standard of care to obtain a contrast enhanced computed tomography scan of the chest, abdomen, and pelvis for pretreatment planning, primary staging, and post treatment disease surveillance. This makes the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In our literature review, we found that intramuscular metastases from urothelial cancer have been reported most commonly in the iliopsoas [ 23 ], with other sites also reported, including the deltoid [ 24 ], rectus abdominis [ 25 ], adductors [ 25 ], sartorius [ 26 ], and gastrocnemius [ 27 ]. Intramuscular metastasis can present as localized pain but can also present as secondary to a compressive effect on surrounding structures [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our literature review, we found that intramuscular metastases from urothelial cancer have been reported most commonly in the iliopsoas [ 23 ], with other sites also reported, including the deltoid [ 24 ], rectus abdominis [ 25 ], adductors [ 25 ], sartorius [ 26 ], and gastrocnemius [ 27 ]. Intramuscular metastasis can present as localized pain but can also present as secondary to a compressive effect on surrounding structures [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy and radiotherapy are utilized in patients who are contraindicated for surgery or as adjunct therapy with palliative debulking surgery to prevent local recurrence [ 39 ]. For intramuscular metastases, chemotherapy and radiotherapy can be administered for pain relief or reduction in mass effect from intramuscular metastases [ 26 , 27 ]. As patients often have widespread metastasis at presentation, surgery is only reserved for those with isolated soft-tissue metastases after a long disease-free interval.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, urothelial carcinoma progresses by local invasion or lymphatic spread with hematogenous spread occurring less often [4]. Some of the most common areas of metastasis include lymph node, lung, and bone [7]. Skeletal muscle metastasis of urothelial carcinoma is extremely rare with less than 20 cases previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…Other cases have been reported in the literature of acrometastasis failing to be appropriately recognised for several reasons 14 15. CT thorax, abdomen and pelvis is often used as the standard workup to screen for distant metastasis; a modality that clearly does not provide imaging of the extremities.…”
Section: Discussionmentioning
confidence: 99%